2015
DOI: 10.11648/j.sjph.20150306.20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Workplace Conditions and Health and Safety Situation in Chemical and Textile Industries of Pakistan

Abstract: The study was conducted to assess the workplace conditions, health and safety situations in textile and chemical industries of one of the commercial cities of Pakistan i.e. Faisalabad. Risk assessment was conducted through qualitative and quantitative assessment methods. The effluents and gases emissions in the textile and chemical mills of Faisalabad were monitored. Results indicated the working conditions in the work place were not conducive for maximum productivity and there was high risk that may be befall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Thus, these industries have a strongly alkaline pH. Similar results were found in another study conducted on textile and chemical industrial wastewater and concluded moderate to strong alkaline water of these industries (Ali et al, 2006;Shah et al, 2015). However, most of the studies showed that the ghee and oil industrial effluents have less pH and EC as compared to the chemical and textile industries.…”
Section: Resultssupporting
confidence: 71%
“…Thus, these industries have a strongly alkaline pH. Similar results were found in another study conducted on textile and chemical industrial wastewater and concluded moderate to strong alkaline water of these industries (Ali et al, 2006;Shah et al, 2015). However, most of the studies showed that the ghee and oil industrial effluents have less pH and EC as compared to the chemical and textile industries.…”
Section: Resultssupporting
confidence: 71%
“…ELMERI is an authoritative and very simple tool for inspection of industrial health and safety, which was presented by the Finland Health Care Institute in 2000 to carry out occupational safety and health inspections. In this method, the occupational safety and health status are examined in seven dimensions including unsafe behaviors, housekeeping, machinery safety, industrial hygiene, ergonomics, commution routes, fire safety, and first aid (11). In order to use the ELMERI index to assess the mosque's safety status, in the first stage, a basic study of the most important safety issues of mosques was collected using standards, regulatory requirements and health and safety regulations, as well as an opinion of safety experts; then, we adapted and modified the items of this index according to the conditions of the mosques in 6 areas: (1) housekeeping (4 items), (2) heating and cooling systems (8 items), (3) environmental health (10 items), (4) building safety (10 items), (5) electrical safety (7 items), and (6) fire safety and emergency response (FSER) (9 items).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, in other studies, high work-related demands, poor interpersonal communication, role ambiguity, working environment, and career development [33] have been identified as the job stressors. erefore, working conditions, as well as the health and safety situation, in the textile and clothing sector organizations of Pakistan were found unfavorable to higher productivity [34]. Multiple hazards such as inadequate physical working conditions along with unacceptable temperature, humidity, and noise levels highlighted the need for training, awareness, and top management commitment [34].…”
Section: Antecedents Of Workmentioning
confidence: 99%
“…erefore, working conditions, as well as the health and safety situation, in the textile and clothing sector organizations of Pakistan were found unfavorable to higher productivity [34]. Multiple hazards such as inadequate physical working conditions along with unacceptable temperature, humidity, and noise levels highlighted the need for training, awareness, and top management commitment [34].…”
Section: Antecedents Of Workmentioning
confidence: 99%